Feasibility and Safety of Permanent Left Bundle Branch Pacing in Patients With Conduction Disorders Following Prosthetic Cardiac Valves - Wei, Hui-Qiang; Li, Hui; Liao, Hongtao; Liang, Yuanhong; Zhan, Xianzhang; Zhang, Qianhuan; Deng, Hai; Wei, Wei; Liao, Zili; Liu, Yang; Liu, Fangzhou; Lin, Weidong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The feasibility and safety of left bundle branch pacing (LBBP) in patients with conduction diseases following prosthetic valves (PVs) have not been well described. Methods: Permanent LBBP was attempted in patients with PVs. Procedural success and intracardiac electrical measurements were recorded at implant. Pacing threshold, complications, and echocardiographic data were assessed at implant and follow-up visit. Results: Twenty-two consecutive patients with atrioventricular (AV) conduction disturbances (10 with AV nodal block and 12 with infranodal block) underwent LBBP. The PVs included aortic valve replacement (AVR) in six patients, mitral valve repair or replacement (MVR) with tricuspid valve ring (TVR) in four patients, AVR with TVR in one patient, AVR with MVR plus TVR in three patients, transcatheter aortic valve replacement (TAVR) in five patients, and MVR alone in three patients. LBBP succeeded in 20 of 22 (90.9%) patients. LBB potential was observed in 15 of 22 (68.2%) patients, including 10 of 15 (66.7%) patients with AVR/TAVR and five of seven (71.4%) patients without AVR/TAVR. AVR and TVR served as good anatomic landmarks for facilitating the LBBP. The final sites of LBBP were 17.9 ± 1.4 mm inferior to the AVR and 23.0 ± 3.2 mm distal and septal to the TVR. The paced QRS duration was 124.5 ± 13.8 ms, while the baseline QRS duration was 120.0 ± 32.5 ms (P = 0.346). Pacing threshold and R-wave amplitude at implant were 0.60 ± 0.16 V at 0.5 ms and 11.9 ± 5.5 mV and remained stable at the mean follow-up of 16.1 ± 10.8 months. No significant exacerbation of tricuspid valve regurgitation was observed compared to baseline. Conclusion: Permanent LBBP could be feasibly and safely obtained in the majority of patients with PVs. The location of the PV might serve as a landmark for guiding the final site of the LBBP. Stable pacing parameters were observed during the follow-up.